2014
DOI: 10.1093/jxb/eru438
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of the PP2A regulatory subunit Tap46 leads to enhanced plant growth through stimulation of the TOR signalling pathway

Abstract: HighlightOur study of Tap46 overexpression suggests that Tap46 enhances plant growth as a positive effector of the TOR signalling pathway. Furthermore, the abundance of Tap46/PP2Ac protein is regulated by TOR activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
61
2
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 72 publications
(66 citation statements)
references
References 61 publications
0
61
2
3
Order By: Relevance
“…MRF1 phosphorylation did not occur without the addition of S6K1 (Supplemental Figure 18A). Arabidopsis S6K1 has a conserved site, T449, which is phosphorylated by the TOR kinase (Xiong and Sheen, 2012;Ahn et al, 2015). We determined MRF1 phosphorylation activities of two mutant forms of S6K1, a phospho-null mutant (T449A) and a phospho-mimetic mutant (T449D), and compared them to normal S6K1 ( Figure 11C).…”
Section: Mrf1 Is Phosphorylated By S6k1 and S6k2 In Vitromentioning
confidence: 99%
See 3 more Smart Citations
“…MRF1 phosphorylation did not occur without the addition of S6K1 (Supplemental Figure 18A). Arabidopsis S6K1 has a conserved site, T449, which is phosphorylated by the TOR kinase (Xiong and Sheen, 2012;Ahn et al, 2015). We determined MRF1 phosphorylation activities of two mutant forms of S6K1, a phospho-null mutant (T449A) and a phospho-mimetic mutant (T449D), and compared them to normal S6K1 ( Figure 11C).…”
Section: Mrf1 Is Phosphorylated By S6k1 and S6k2 In Vitromentioning
confidence: 99%
“…Agrobacterium-mediated transient expression was performed using Agrobacterium C58C1 strain as described (Ahn et al, 2015), except for BiFC experiments that used the GV3101 strain. Overnight-grown Agrobacterium culture was resuspended in infiltration medium (10 mM MES-KOH, pH 5.7, 10 mM MgSO 4 , and 500 mM acetosyringone) to different OD 600 depending on experiments (described below) and incubated for 2 h at room temperature, before infiltration into Nicotiana benthamiana leaves.…”
Section: Agrobacterium-mediated Transient Expressionmentioning
confidence: 99%
See 2 more Smart Citations
“…In plants, PP2As play crucial roles in hormone signal transduction and abiotic stress response (DeLong, 2006). Overexpression of some PP2As can enhance plant growth and increase drought tolerance in transgenic plants (Luo et al, 2006;Xu et al, 2007;Ahn et al, 2015). However, another study reported a contradictory result for the role of PP2A by overexpressing and knocking out the C1 subunit gene in Arabidopsis (Pernas et al, 2007).…”
Section: Introductionmentioning
confidence: 99%